Does Facebook functionality boost civic engagement among Malaysian youths? - Abd Latib, Latifah; Bolong, Jusang; Ahmad Ghazali, Akmar Hayati; Osman, Mohd Nizam (International Organization Center of Academic Research, 2016)
Civic engagement is an important process in which multiracial youth embrace the responsibilities to actively participate in public life to help shape and strengthen the local community. More recently, the creative application of technology such as social media application has attracted considerable attention how to fostering youth engagement. By engaging youths through social media such as Facebook as a two-way communications tool, young people can have a say in the governance of their local communities as well as broader society. Although it is clear that social media such as Facebook is very powerful tool for communication, many of young people are unable to identify the Facebook functionality in term of developing communication strategies and to allocate the resources effectively. The main reason behind the ineptitude is deficiency of understanding the definition and the functionality of Facebook itself. With an emerging impact of social media specifically Facebook in the organizational domain, more knowledge is needed on how to design and use social media to motivate youth civic engagement. Taking this into account this study sought to find whether there is a relationship between Facebook functionality and civic engagement to boost youth civic engagement. Based on the literature reviews of civic engagement factors and the functionality of Facebook, a conceptual framework of relationship was proposed and developed to examine the relationships between the Facebook functionality and civic engagement. The study will also provide the direction and guidance to the youths in managing the functionality of Facebook in their communities and also if any benefits for them to use Facebook in communication with the public. Youths can also monitor and understand how social media such as Facebook activities vary in terms of their function and impact, so as to develop a congruent social media strategy based on the appropriate balance of functionality of Facebook for their community.